2011
DOI: 10.1007/s10803-011-1236-7
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Parent-Report of Child Autism Spectrum Disorder Diagnosis to a Web-Based Autism Registry

Abstract: Growing interest in autism spectrum disorder (ASD) research requires increasingly large samples to uncover epidemiologic trends; such a large dataset is available in a national, web-based autism registry, the Interactive Autism Network (IAN). The objective of this study was to verify parent-report of professional ASD diagnosis to the registry's database via a medical record review on a sample of IAN Research participants. Sixty-one percent of families agreed to participate; 98% (n = 116) of whom provided docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(184 citation statements)
references
References 25 publications
7
177
0
Order By: Relevance
“…We utilized the SRS short form, which consists of 18 items scored from 0 ("never true") to 3 ("almost always true") and that reflects the parent's observation of the child's social behavior over the past 6 months. The 18-item SRS total score has been shown to correlate between 0.93 and 0.99 with the total score of the full SRS version in three different large studies (Constantino & Todd, 2003;Daniels et al, 2012;White et al, 2017). The SRS 18-item measure provides a valid quantitative measure of subclinical and clinical autistic traits and covers both the social communication/interaction and restricted/ repetitive patterns of behavior, interests, or activities.…”
Section: Autistic Traitsmentioning
confidence: 99%
“…We utilized the SRS short form, which consists of 18 items scored from 0 ("never true") to 3 ("almost always true") and that reflects the parent's observation of the child's social behavior over the past 6 months. The 18-item SRS total score has been shown to correlate between 0.93 and 0.99 with the total score of the full SRS version in three different large studies (Constantino & Todd, 2003;Daniels et al, 2012;White et al, 2017). The SRS 18-item measure provides a valid quantitative measure of subclinical and clinical autistic traits and covers both the social communication/interaction and restricted/ repetitive patterns of behavior, interests, or activities.…”
Section: Autistic Traitsmentioning
confidence: 99%
“…As part of the larger study, participants were recruited online through various autism organizations, including the Interactive Autism Network, an online research registry for caregivers of children with ASD, which recently authenticated the parent-report ASD diagnosis in their registry (Daniels et al, 2012). Children included in this study had a caregiver-reported diagnosis of an ASD, including autism or autistic disorder, Asperger's disorder, and pervasive developmental disorder-not otherwise specified (American Psychiatric Association, 2000).…”
Section: Participantsmentioning
confidence: 99%
“…The external reviewer (i.e., not an author of this study) assessed the medical documentation for objective indications of ASD. Similar non-research diagnoses were compared to direct gold standard ADOS testing, resulting in 93% agreement in the ASD diagnosis [13] , and reconfirmed in a follow-up study [14] . Adults who were suspected of being on the autism spectrum (e.g., high-functioning autism or Asperger's syndrome) were administered the Autistic Spectrum Quotient [7] , since the Autism Diagnostic Interview-Revised [15] would not be reliable in older adults due to difficulty of self-reporting on very early childhood events.…”
Section: Prodigy Criteriamentioning
confidence: 89%